Are consumer decision-making phenomena a fourth market failure? - Pete Lunn (The Economic and Social Research Institute (ESRI), 2013)
This paper challenges the increasingly common view that the findings of behavioural economics constitute a fourth type of market failure. The market failure framework elevates the standard competitive market model to the status of an ideal. It provides us with tools to identify departures from the ideal model and to deduce a direction policy might take to restore it. Many behavioural phenomena also imply departures from the ideal model. Yet rather than allowing us to deduce a good direction for policy, the findings question the legitimacy and usefulness of this deductive theoretical framework for policy analysis. Two policy problems are highlighted here: the validity of inferring that consumers' choices after an intervention improve outcomes relative to their previous choices, and the potential for distributional consequences when policy alters consumers' choices. The paper concludes that, given these problems, conceiving of the relevant behavioural phenomena as an additional form of market failure is potentially to misunderstand their implications for consumer and competition policy.
Keywords: D03; D18; L96; 330; Market Failure; Decision-making biases; Behavioural economics; Regulation